Fractional frequency reuse interference mitigation in LTE femtocell network / Wan Nurdiyana Wan Mat - Wan Mat, Wan Nurdiyana (2014)
The demand of wireless services through the cellular networks is ever-increasing. Femtocell has a strong potential for increasing the efficiency, improvements of cell coverage and network capacity of next-generation mobile networks. In Long Term Evolution (LTE) technology has developed a femtocell for indoor coverage extension. Both these problems can be solved by deploying femtocells in LTE networks. Interference occurs between newly added femtocell and pre existing macrocell as macrocell and femtocell share same frequency band. Macrocell-femtocell interference management is biggest issue when talk about LTE femtocell networks. Effective frequency allocation scheme should be used for macrocell-femtocell interference management in LTE femtocell network. Various frequency allocation schemes used for interference management in LTE femtocell networks are discussed in this paper.